Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Mapping the education data ecosystem in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
Keywords: _EdTechHub_Output; _MELA_seen

GIS for Education Working Group launches to promote data-driven decision-making - the Education Commission (the Education Commission, 2021)
Around the world, individuals are using maps to power everyday decisions: how do I navigate from my home to the nearest hospital? How many supermarkets are in my community? What public transportation is available for me to take to work?
Keywords: _yl:b

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

Mapping education data in sub-Saharan Africa: Our experience from the Unlocking Data campaign and Sierra Leone - Unlocking Data (2021)

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

The global stakes of digitalization in education - Haßler, Björn (The global stakes of digitalization in education (Uganda), 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _zenodo:submitted

GIS for Education Working Group launches to promote data-driven decision-making - The Education Comission (the Education Commission, 2021)
Around the world, individuals are using maps to power everyday decisions: how do I navigate from my home to the nearest hospital? How many supermarkets are in my community? What public transportation is available for me to take to work?

Concept on mapping technical and vocational educational and training data in Kenya - Ministry of Education (State Department for Vocational and Technical Training, 2021)

The last mile in school access: Mapping education deserts in developing countries - Rodriguez-Segura, Daniel; Kim, Brian Heseung (Development Engineering, 2021)
With recent advances in high-resolution satellite imagery and machine vision algorithms, fine-grain geospatial data on population are now widely available: kilometer-by-kilometer, worldwide. In this paper, we showcase how researchers and policymakers in developing countries can leverage these novel data to precisely identify “education deserts” – localized areas where families lack physical access to education – at unprecedented scale, detail, and cost-effectiveness. We demonstrate how these analyses could valuably inform educational access initiatives like school construction and transportation investments, and outline a variety of analytic extensions to gain deeper insight into the state of school access across a given country. We conduct a proof-of-concept analysis in the context of Guatemala, which has historically struggled with educational access, as a demonstration of the utility, viability, and flexibility of our proposed approach. We find that the vast majority of Guatemalan population lives within 3 km of a public primary school, indicating a generally low incidence of distance as a barrier to education in that context. However, we still identify concentrated pockets of population for whom the distance to school remains prohibitive, revealing important geographic variation within the strong country-wide average. Finally, we show how even a small number of optimally-placed schools in these areas, using a simple algorithm we develop, could substantially reduce the incidence of education deserts in this context. We make our entire codebase available to the public – fully free, open-source, heavily documented, and designed for broad use – allowing analysts across contexts to easily replicate our proposed analyses for other countries, educational levels, and public goods more generally.
Keywords: Access to education; Education deserts; Education in developing countries; School placement

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Mapping education data in sub-Saharan Africa - Lawson, Laté; Heady, Lucy (Education Sub Saharan Africa (ESSA), 2021)

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Keep Kenya Learning: Helping Caregivers Support Learning at Home Sprint 1 - Mbatha, FaithMbithe; Crook, Rebecca; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org Our research indicates that guidance and resources are necessary but insufficient in equipping caregivers to support their children’s learning. In Sprint 1, caregiver confidence and community emerged as important enablers of home learning. In our interviews, caregivers communicated how they felt limited by their lack of or outdated education. Global interventions indicate that reinforcing a sense of community for caregivers and enabling them to learn from modelling by trusted messengers are pathways to building greater engagement. Caregivers in both rural and urban communities expressed a willingness to engage with SMS (short message service) and online educational resources. However, it is clear that resource design must be: Accessible and understandable Credible and trusted Relevant and actionable.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted; ⛔ No INSPIRE recid found

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Technologies for Data Collection, Processing and Communication in Education in Emergencies: Mapping Practices and Opportunities in the MENA region and Globally - FHI360; USAID (2021)

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon,; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted